Hukum Merenggangkan Shaf dalam Shalat Berjamaah Saat Pandemi Covid 19 - Imam Syarbini (UNIVERSITAS BONDOWOSO, 2021)
Prayer is worship that contains speech, actions that begin with Takbiratul Ihram and end with greetings with certain conditions and pillars. From the understanding of etymology and terminology, it can be understood that prayer from the beginning to the end, all contains prayer, confession of sins and glorification of Allah. Therefore, someone who makes prayers means he is praying a lot and doing self-cleansing both physically (Wudhu ') and non-physically (repentance). This is an important meaning of prayer for humans. Moreover, if done in congregation, Allah will multiply his palahas up to 27 degrees compared to praying alone, eliminating all mistakes and protecting them from the devil. In congregational prayer, it is recommended to straighten and tighten the rows, many hadiths suggest that even the Prophet arranged himself to close the rows Along with the spread of the corona virus that has swept the world, including Indonesia, to prevent the spread of the virus, the government has implemented four healthy things that must be obeyed by the community, namely; wear personal protective equipment in the form of a mask, clean your hands regularly by washing your hands with soap with running water or using an alcohol-based hand sanitizer, , maintaining a minimum physical distance of 1 meter from other people to avoid getting droplets from people who are talking, and increasing endurance by applying a clean and healthy lifestyle. With these four rules, everyone must maintain a distance / psychological distencing from other people at least 1 meter, including in places of worship, such as mosques or mushalla, when praying in congregation, between the congregation is one meter away. Regarding the law of stretching out the shaf in congregational prayer, here the ulama 'punishes Makruh, because the prohibition does not have direct arguments, but a prohibition that is understood from the commandment of the sunnah, , the consequences if it is violated will not result in the invalidation of prayers, but only do not get 25 or 27 degrees of priority . According to Imam Ramli, irregular shaf does not reduce the fadhilah of the congregation, it only removes the virtue of the shaf. Such chaos, if under normal conditions, if under abnormal conditions, such as having to maintain a minimum physical distance of 1 meter from other people, does not diminish the reward of 25 or 27 degrees of virtue.